AMMONOID STRATIGRAPHY AND SEDIMENTARY EVOLUTION ACROSS THE PERMIAN - TRIASSIC BOUNDARY IN EAST GREENLAND - Bjerager M.; Seidler L.; Surlyk F.; Stemmerik L. (My University, 2006)
East Greenland is a classical area for the study of the Permianearliest Triassic H.trivialeTriassic boundary. The new ammonoid data indicate that deposition was continuous across the Permianmudstone contact in basinal areas of Hold With Hope, northern and southern Jameson Land. Correlation of the ammonoid stratigraphy with the FAD of Hindeodusparvus, which defines the base of the Triassic in Global Stratotype Section and Point (GSSP) in Meishan, China, suggests that the Hypophicerastriviale Zone is to be referred to the uppermost Permian, whereas the H.martini Zone is lowermost Triassic. Accordingly, the end-Permian marine and terrestrial extinctions and associated isotope changes as well as the subsequent adaptive radiations in East Greenland took place in latest Permian time. New Boreal faunas and floras were well established and diversified in the Hypophicerastriviale Zone prior to the beginning of the Triassic, and the Permian–Triassic boundary, in its present definition, is no longer reflecting major changes in the Earth system. It would have been fortunate if a GSSP were defined in a protracted section at a point of major environmental perturbations, marked by isotope excursions, chemical anomalies and mass extinction, rather than in the strongly condensed section like Meishan at a point which post-dates all significant events.
Keywords: Triassic; Permian; Mesozoic::Triassic; Мезозой::Триасовая; Paleozoic::Permian; Палеозой::Пермская